PENGEMBANGAN PROGRAM BELAJAR MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Rudy Setiawan; Elita Mega Selvia Wijaya; Maria Tanggu Todhu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
This study aims to improve student learning outcomes based on Student Worksheets using the Realistic Mathematics Education approach. Realistic Mathematics Education is a learning concept that presents a material in the form of problems that must be solved by students based on understanding the concepts of everyday student life. This research is a research development or Research and Development (R&D) adapted from the ADDIE development model, with 5 stages of development, namely: 1) Analysis (analysis); 2) Design (design); 3) Development (development); 4) Implementation (implementation); and 5) Evaluation. Based on the analysis of the assessment data from the questionnaire results of teaching materials filled out by students of SMPN 16 Malang class VIIIA, the results showed that the teaching materials developed were in the very good category with an average score of 87%. This shows that the teaching materials developed are very valid.